A waterproof environment-friendly polyester fiber sound absorption board and a preparation method thereof

CN122980585APending Publication Date: 2026-10-27FOSHAN HENGCHU ENVIRONMENT FACILITY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611174974.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

钢板、铅箔等异质材料无法与聚酯纤维共同回收,废弃板材需分离处理,使聚酯纤维板丧失了可循环的核心环保优势

Benefits of technology

[0019]与现有技术相比,本发明的有益效果是:本发明公开了一种高阻尼皮芯微孔聚酯纤维防水隔音板及其制备方法。隔音板采用皮芯微孔聚酯短纤维为主体骨架,以低熔点共聚酯纤维和聚己内酯粉末为双级粘结体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of polyester fiber, and particularly relates to a waterproof and environment-friendly polyester fiber sound absorption board and a preparation method thereof; the sound absorption board comprises three components of skin-core microporous polyester fiber, low-melting-point polyester fiber and polycaprolactone powder; the skin-core microporous polyester fiber is 70-80 parts, the low-melting-point copolyester fiber is 20-25 parts, and the polycaprolactone powder is 10 parts in terms of weight parts. The core functional unit of the skin-core microporous polyester fiber is a core microporous structure, which is a skin-core structure with dense skin layer and closed microporous-rich core layer, and is used for providing lightweight, waterproof barrier and sound wave multiple scattering dissipation; a dynamic covalent cross-linking network based on furan-bismaleimide reversible bond is also embedded in the core layer matrix, and is used for imparting high damping characteristics to the fiber, converting vibration energy and sound energy into heat energy dissipation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester fiber technology, and in particular to a waterproof and environmentally friendly polyester fiber sound-absorbing board and its preparation method. Background Technology

[0002] Currently, porous fiber acoustic panels are widely used in the construction and transportation sectors for noise control. Among them, polyester fiberboard has gradually become the mainstream choice for indoor acoustic materials due to its advantages such as hydrophobicity, mildew resistance, and recyclability. However, there is a fundamental contradiction between sound insulation performance, lightweighting, and sound absorption performance: to improve sound insulation, the surface density of the board needs to be increased or a heavy layer needs to be sandwiched, but this leads to increased weight and cost, and excessive density will close the pores between fibers, reducing the sound absorption coefficient; on the other hand, to achieve lightweight and high sound absorption, the fiberboard needs to maintain low density and interconnected pores, but such structures have insufficient surface density and limited airborne sound isolation capabilities. In addition, the contradiction between the low-frequency sound absorption capacity of porous fiberboard and structural stiffness is also prominent: low-frequency noise has a long wavelength and needs to be dissipated by means of a resonant cavity or by increasing the depth of the cavity behind it, but such structural designs will sacrifice the bending stiffness and dimensional stability of the board itself. Pure polyester fiberboard is prone to creep and sagging during long-term use. If the hot-pressing density is increased to improve rigidity, the porosity of the board will decrease, and the mid-to-high frequency sound absorption performance will deteriorate simultaneously.

[0003] To address the aforementioned contradictions, several improvement solutions have emerged in existing technologies. One solution involves sandwiching heavy barrier layers such as steel plates, lead plates, or highly filled resin films into the fiberboard to create a composite structure. Another solution uses bicomponent core-sheath fibers, utilizing the low-melting-point polyester in the sheath layer to form a rigid skeleton through thermal bonding, while the core layer retains a hollow structure. However, dissimilar materials such as steel plates and lead foil cannot be recycled along with the polyester fibers, requiring the separation of waste boards and causing the polyester fiberboard to lose its core environmental advantage of recyclability. Furthermore, traditional hollow polyester fibers have a wall thickness of only a few micrometers, making the hollow structure prone to collapse during hot pressing, resulting in an actual cavity retention rate of less than 30%, significantly compromising lightweight and acoustic performance.

[0004] Therefore, existing technologies suffer from the problem of difficulty in simultaneously achieving lightweight, high sound insulation, high damping, waterproofing, and full recyclability. There is a lack of an integrated solution from fiber molecular structure to the macroscopic configuration of the board, which severely restricts the application and development of polyester fiber sound insulation boards in humid environments and scenarios with high sound insulation requirements. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a waterproof and environmentally friendly polyester fiber sound-absorbing board and its preparation method. It comprises three components: sheath-core microporous polyester fiber, low-melting-point polyester fiber, and polycaprolactone powder. By weight, the sheath-core microporous polyester fiber comprises 70 to 80 parts, the low-melting-point copolyester fiber comprises 20 to 25 parts, and the polycaprolactone powder comprises 10 parts. The core functional unit of the sheath-core microporous polyester fiber is a core layer microporous structure, which is a sheath-core structure with a dense sheath layer and a core layer rich in closed-cell micropores, providing lightweight, waterproof barrier, and multiple sound wave scattering dissipation. The core layer matrix also embeds a dynamic covalent cross-linked network based on furan-bismaleimide reversible Diels-Alder bonds, which imparts high damping properties to the fiber, converting vibrational and acoustic energy into heat energy for dissipation.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board, comprising the following steps: Step S1: Weigh 75-80 parts by weight of sheath-core microporous polyester fiber short cuts and mix them with 15-20 parts of low melting point polyester fiber and 10 parts of polycaprolactone powder. Feed the mixture into a fiber mixing and opening machine, comb it, lay it into a web and repeat the process to obtain a fiber web. Step S2: The fiber mesh is fed into a double-sided needle punching machine for pre-reinforcement. Then, 8 layers of pre-reinforced fiber mesh are stacked and hot-pressed. First, it is hot-pressed at a temperature of 75℃ and a pressure of 0.3MPa for 5 minutes, and then hot-pressed at a temperature of 90℃ and a pressure of 1MPa for 4 minutes. Then, water-based polyurethane emulsion is sprayed on its surface, and it is dried at 80℃ for 5 minutes. After cutting, a waterproof and environmentally friendly polyester fiber sound-absorbing board is obtained.

[0007] Furthermore, in step S1: the areal density of the fiber web is 300-320 g / m². 2 In step S2: the solid content of the waterborne polyurethane emulsion is 5%, and the spraying amount is 5 g / m². 2 .

[0008] The core-sheath microporous polyester fiber is obtained through the following steps: Step A1: Mix and dry the mixed polyester material, azodicarbonamide, zinc oxide and white oil to obtain the core layer foaming premix; mix and dry the polyethylene terephthalate-polyethylene glycol block copolyester and hydrophobic nano silica to obtain the skin layer premix. Further, by weight: the amount used in step A1 is: 90-92 parts of mixed polyester material, 5 parts of azodicarbonamide, 1.5 parts of zinc oxide and 0.5 parts of white oil; the amount used in step A2 is: 98 parts of polyethylene terephthalate-polyethylene glycol block copolyester and 2 parts of hydrophobic nano silica; the polyethylene glycol content in the polyethylene terephthalate-polyethylene glycol block copolyester is 20 wt%.

[0009] Step A2: Spinning is carried out using a core-sheath composite spinning machine. The core layer foamed premix and the sheath layer premix are fed into a twin-screw extruder and melt-extruded. The fibers are then produced by the spinneret, bundled, drawn and stretched, wound, and then sent to a vacuum oven for annealing to obtain core-sheath microporous polyester fibers. Further, in step A2: the volume ratio of the core layer foam premix and the skin layer premix is ​​controlled by a metering pump to be 75:25 or 60:40; the melt extrusion temperatures of the core layer foam premix and the skin layer premix are 260℃ and 240℃, respectively; the spinneret has annular core-skin holes with 9 holes and a hole diameter of 0.3mm; the winding speed is 600m / min and the stretching ratio is 1.2 times; the annealing pressure is 100Pa, and during annealing, it is first held at 60℃ for 4h and then held at 90℃ for 20h.

[0010] The mixed polyester material is prepared by the following steps: Step B1: Diethyl itaconic acid, furfurylamine and acetic acid were mixed and reacted for 18 h under nitrogen protection, stirring at 300 rpm and temperature at 50 °C. After cooling, the mixture was washed with saturated sodium bicarbonate solution, separated, rotary evaporated and dried to obtain the side-chain furan monomer. Furthermore, in step B1, the ratio of diethyl itaconic acid, furfurylamine, and acetic acid is 10g:5.2g:0.1mL.

[0011] Step B2: Hexanediol, 1,4-butanediol, side-chain furan monomer, n-butyl titanate and hydroquinone were mixed and stirred for 30 min under nitrogen protection at a stirring rate of 300 rpm and a temperature of 90℃. The temperature was then increased to 120℃ and stirred for 1 h. Finally, the temperature was increased to 190℃ and reacted for 4 h. The vacuum was drawn to a pressure of 100 Pa and reacted at 200℃ for 3 h. After cooling and drying, the side-chain furan copolyester was obtained. Furthermore, in step B2, the ratio of hexanediol, 1,4-butanediol, side-chain furan monomer, n-butyl titanate, and hydroquinone is 4.5g:7g:3.2g:0.005mL:0.03g.

[0012] Step B3: Dry polyethylene terephthalate, side-chain furan copolyester and 4,4'-bismaleimide diphenylmethane and mix with antioxidant 1010, hydroquinone and calcium stearate, feed into a twin-screw extruder for melt extrusion, water-cooled granulation, and drying to obtain a mixed polyester material; Furthermore, in step B3, the ratio of polyethylene terephthalate, side-chain furan copolyester, 4,4'-bismaleimide diphenylmethane, antioxidant 1010, hydroquinone, and calcium stearate is 7g:3.5g:0.7g:0.05g:0.005g:0.03g; wherein the twin-screw extruder head temperature is 250℃, the screw speed is 200rpm, and the residence time is 2min.

[0013] Furthermore, in the above reaction process: In step B1, diethyl itaconic acid, as an α,β-unsaturated ester, undergoes a Michael addition reaction with the primary amine group of furfurylamine under acetic acid catalysis due to its electron-deficient double bond. The amino group of furfurylamine acts as a nucleophile, attacking the β-carbon of diethyl itaconic acid to form a carbon-nitrogen bond, thus attaching the furan ring to the diester backbone through a stable secondary amine bond. A solvent-free, low-temperature bulk reaction is employed. Acetic acid provides a weakly acidic environment to suppress the amidation side reaction between the ester group and the amine, while protonating part of the amine group to control the reaction rate. The product is washed with saturated sodium bicarbonate to remove unreacted trace amounts of acid and amine salt, yielding a side-chain furan monomer.

[0014] In step B2, adipic acid provides flexible aliphatic segments, 1,4-butanediol is the diol component, and the side-chain furan intermediate participates in copolymerization as a diester containing furan side groups. Tetrabutyl titanate catalyzes transesterification and esterification reactions, while hydroquinone acts as a free radical inhibitor during the polycondensation stage, preventing oxidation or thermal crosslinking of the unsaturated furan ring at high temperatures. The esterification stage employs a stepped heating process, allowing each component dicarboxylic acid to react sequentially with butanediol, gradually removing condensation water. The polycondensation stage is conducted at 200°C and 100 Pa, continuously removing low-molecular-weight byproducts and driving chain growth equilibrium to obtain a side-chain furan copolyester. The introduction of adipic acid segments lowers the glass transition temperature of the copolyester, significantly lower than that of polyethylene terephthalate, providing a basis for the segmental mobility during subsequent fiber solid-state annealing.

[0015] In step B3, polyethylene terephthalate (PET) serves as the continuous phase matrix, with furan copolyester as the functional phase dispersed within it. 4,4'-bismaleimide diphenylmethane is uniformly distributed in nanoclusters. The extrusion temperature is set at 250°C, which is significantly higher than the reverse reaction temperature of the furan-maleimide DA bond. Therefore, during this high-temperature processing stage, no DA crosslinking reaction occurs between the furan side groups and bismaleimide, and both exist in the melt in an unreacted state. Antioxidant 1010 provides primary antioxidant protection, while hydroquinone acts as an additional free radical inhibitor. Its dual function is to inhibit the free radical self-polymerization of bismaleimide at high temperatures, preventing the formation of irreversible polyimide; and to inhibit the thermo-oxidative ring-opening degradation of the furan ring. Immediately after extrusion, the material is water-cooled, cooling to below the glass transition temperature within seconds, thus fixing and uniformly dispersing the furan and maleimide groups in the masterbatch.

[0016] In step A2, the skin layer is made of polyethylene terephthalate-polyethylene glycol block copolyester (PET-PEG). The addition of hydrophobic nano-silica improves the melt strength and surface hydrophobic angle of the skin layer, causing it to accumulate on the fiber surface during the spinning shear field and form a hydrophobic shell. In the core layer foaming premix, azodicarbonamide decomposes rapidly at a high temperature of 260°C, producing nitrogen and carbon monoxide gases. Zinc oxide acts as an activator, lowering the decomposition initiation temperature and enabling foaming to be triggered synchronously when the melt enters the spinneret. The skin and core melts converge within the annular spinneret. The skin layer cools and solidifies first due to contact with the low-temperature side airflow, forming a dense, bubble-free skin layer. The supersaturated gas inside the core layer uniformly nucleates and expands under the drive of a sudden pressure drop and temperature gradient, forming a large number of closed-cell micropores, which are then encapsulated and fixed by the high-viscosity melt of the core layer matrix. Stretching and heat setting improve fiber orientation and enhance the densification of the skin layer. During this stage, furan and bismaleimide in the fiber remain unreacted because the spinning temperature is too high, far exceeding the DA bond stabilization temperature.

[0017] In the latter part of step A2, the shaped fiber undergoes vacuum low-temperature solid-state annealing, which is the core step in imparting high damping properties to the fiber. Under a 100 Pa vacuum environment, the first stage involves holding at 60°C for 4 hours, allowing the free bismaleimide molecules in the core matrix to acquire sufficient diffusion kinetic energy and move through the intersegmental gaps in the amorphous region of the fiber to the vicinity of the furan side groups. In the second stage, the temperature is raised to 90°C and held for 20 hours. The amorphous region segments exhibit sufficient mobility, and the furan ring and maleimide groups undergo a forward Diels-Alder cycloaddition reaction under thermodynamic drive, gradually forming a slightly cross-linked network connected by reversible covalent bonds. This cross-linked network achieves high damping through two mechanisms: first, the reversible breakage and recombination of dynamic covalent bonds under stress consumes a large amount of mechanical energy; second, the restricted movement of chain segments between cross-linking points enhances viscoelastic internal friction, increasing the fiber loss factor tanδ. Furthermore, the low-temperature annealing avoids the damage to the microporous structure caused by high-temperature treatment, ensuring the complete preservation of the cortex density and the closed-cell morphology of the core.

[0018] In steps S1 and S2, a two-stage bonding strategy was employed in the compounding of the core-sheath microporous short fibers, low-melting-point copolyester fibers, and polycaprolactone powder. The polycaprolactone powder melts during hot pressing, forming flexible, elastic bonding points at fiber intersections, providing initial shaping for the network. By adjusting the pressure to 1 MPa, the fiber web is compressed, while the fiber sheath retains its hydrophobic properties due to the presence of surface nano-silica. A water-based polyurethane emulsion is then sprayed onto the surface and dried at 80°C to form an extremely thin, continuous film, sealing the micropore openings and increasing the contact angle of the board, but the film layer is extremely thin. The highest temperature during the entire board-making process is only 90°C, far below the reverse reaction temperature of the DA bond, ensuring the complete preservation of the dynamic cross-linked network within the fibers and maintaining the board's damping performance.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention discloses a high-damping core-sheath microporous polyester fiber waterproof sound insulation board and its preparation method. The sound insulation board uses core-sheath microporous polyester short fibers as the main skeleton and low-melting-point copolyester fibers and polycaprolactone powder as a two-stage bonding system.

[0020] This invention employs a low-temperature solid-state annealing followed by crosslinking, combined with a high-temperature blending process, to successfully construct a dynamic covalent crosslinking network of DA in polyester fibers. During the high-temperature melt processing stage, furan and bismaleimide are uniformly fixed in the matrix in an unreacted state using free radical inhibitors and rapid cooling. In the low-temperature vacuum annealing stage after fiber forming, the mobility of chain segments above the matrix's glass transition temperature is utilized to induce a forward Diels-Alder reaction in the solid state, forming a reversible crosslink. This step-by-step strategy resolves the contradiction between the high-temperature processing conditions of polyester and the thermodynamic window for low-temperature DA bond formation, thereby increasing the loss factor tanδ of the final fiber. This fundamentally endows the sound insulation board with high damping characteristics, effectively suppressing the sound insulation trough at the matching frequency and structural vibration noise.

[0021] This invention employs a core-sheath composite spinning process combined with core layer chemical foaming to construct a structure within a single fiber: a dense sheath and a core layer rich in closed-cell micropores. The sheath is made of PET-PEG block copolyester containing nano-silica, which rapidly cools to form a dense layer, providing a waterproof barrier and fiber strength. The core layer, formed by the decomposition of azodicarbonamide, has closed pores that reduce fiber density while simultaneously creating a multi-scattering interface for sound waves, enhancing sound energy dissipation. This structure solves the problem of traditional hollow fiber pore walls easily collapsing during hot pressing. The micropores are dispersed within a continuous polyester matrix in the core layer, resulting in significantly better resistance to compression deformation than single-pore hollow fibers.

[0022] This invention employs a two-stage bonding hot-pressing molding scheme: polycaprolactone melts first during low-temperature hot pressing at 75℃ to form elastic nodes, while low-melting-point copolyester fibers provide a rigid skeleton during subsequent heating. This scheme ensures that the maximum hot-pressing temperature does not exceed 90℃, far below the initiation temperature of the DA bond reverse reaction, thus completely preserving the high-damping crosslinking network of the fibers. Simultaneously, the all-polyester system of PET-based fibers + copolyester bonding fibers + aliphatic polyester guarantees that waste from the boards can be recycled through hot pressing or chemical depolymerization, truly meeting the green requirements of the entire life cycle of environmentally friendly waterproof and soundproof boards. Detailed Implementation

[0023] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.

[0024] Furthermore, in the following preparation examples, embodiments, and comparative examples: the low-melting-point polyester fiber is from Longta Chemical Fiber, model LMF; the hydrophobic nano-silica is Cabot TS720; and the waterborne polyurethane emulsion is Chuangxin CX-7050B.

[0025] Preparation Example 1: The side-chain furan copolyester was prepared by the following steps: Step B1: Mix 10g diethyl itaconic acid, 5.2g furfurylamine and 1mL acetic acid, and react for 18h under nitrogen protection, stirring at 300rpm and temperature at 50℃. After cooling, wash with saturated sodium bicarbonate solution, separate the contents, evaporate by rotary evaporation, and dry to obtain the side-chain furan monomer. Step B2: Mix 4.5g hexanediol, 7g 1,4-butanediol, 3.2g side-chain furan monomer, 0.005mL tetrabutyl titanate and 0.03g hydroquinone. Stir for 30min under nitrogen protection, stirring at 300rpm and 90℃. Then raise the temperature to 120℃ and stir for 1h. Finally, raise the temperature to 190℃ and react for 4h. Evacuate to a pressure of 100Pa and react at 200℃ for 3h. Cool and dry to obtain side-chain furan copolyester.

[0026] Preparation Example 2: The mixed polyester material was prepared by the following steps: Step B3: 7g of polyethylene terephthalate, 3.5g of furan copolyester with side group from Preparation Example 1 and 0.7g of 4,4'-bismaleimide diphenylmethane were dried and mixed with 0.05g of antioxidant 1010, 0.005g of hydroquinone and 0.03g of calcium stearate. The mixture was then fed into a twin-screw extruder for melt extrusion. The die temperature of the twin-screw extruder was 250℃, the screw speed was 200rpm, the residence time was 2min, and the mixture was water-cooled, granulated, and dried to obtain the mixed polyester material. Preparation Example 3: Compared with Preparation Example 2, the amount of 4,4'-bismaleimide diphenylmethane in step B3 was adjusted from 0.7g to 1.0g, while the other steps were the same.

[0027] Preparation Example 4: Compared with Preparation Example 2, the amount of 4,4'-bismaleimide diphenylmethane in step B3 was adjusted from 0.7g to 0.4g, while the other steps were the same.

[0028] Comparative Preparation Example 1: Compared to Preparation Example 2, Comparative Preparation Example 1 omits 4,4'-bismaleimide diphenylmethane in step B3, while the other steps remain the same.

[0029] Comparative Preparation Example 2: Compared to Preparation Example 2, the hydroquinone in step B3 was omitted, while the other steps remained the same.

[0030] Example 1: A method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board, comprising the following steps: Core-sheath microporous polyester fibers are obtained through the following steps: Step A1: Mix and dry 92 parts of the mixed polyester material, 5 parts of azodicarbonamide, 1.5 parts of zinc oxide and 0.5 parts of white oil from Preparation Example 2 to obtain the core layer foaming premix; mix and dry 98 parts of polyethylene terephthalate-polyethylene glycol block copolyester with a polyethylene glycol content of 20 wt% and 2 parts of hydrophobic nano silica to obtain the skin layer premix; Step A2: Spinning is carried out using a core-sheath composite spinning machine. The core layer foamed premix and the sheath premix with a volume ratio of 75:25 are fed into a twin-screw extruder and melt-extruded. The melt extrusion temperatures of the core layer foamed premix and the sheath premix are 260℃ and 240℃, respectively. The fibers are extruded from a spinneret with annular core-sheath holes, 9 holes with a diameter of 0.3mm. The fibers are bundled, stretched, and wound at a speed of 600m / min and a stretch ratio of 1.2. Then, the fibers are sent to a vacuum oven for annealing at a pressure of 100Pa. During annealing, the fibers are first held at 60℃ for 4 hours and then at 90℃ for 20 hours to obtain core-sheath microporous polyester fibers.

[0031] Step S1: Weigh 75 parts by weight of core-sheath microporous polyester fiber short chopped and mix with 20 parts by weight of low melting point polyester fiber and 10 parts by weight of polycaprolactone powder. Feed the mixture into a fiber mixing and opening machine, card it, lay it into a web and repeat the process. The areal density of the fiber web is 312 g / m². 2 To produce a fiber web; Step S2: The fiber web is fed into a double-sided needle punching machine for pre-reinforcement. Then, eight layers of pre-reinforced fiber web are stacked and hot-pressed. First, it is hot-pressed at 75℃ and 0.3MPa for 5 minutes, then at 90℃ and 1MPa for 4 minutes. Finally, a water-based polyurethane emulsion with a solid content of 5% is sprayed onto its surface at a rate of 5 g / m². 2 The material is dried at 80℃ for 5 minutes, then cut to obtain a waterproof and environmentally friendly polyester fiber sound-absorbing board.

[0032] Example 2: Compared with Example 1, the volume ratio of the core layer foaming premix and the skin layer premix in step A2 is adjusted from 75:25 to 60:40, while the other steps are the same.

[0033] Example 3: Compared with Example 1, the amount of core-sheath microporous polyester fiber in step S1 is adjusted from 75 parts to 80 parts, and the amount of low melting point copolyester fiber is adjusted from 20 parts to 15 parts accordingly. The other steps are the same.

[0034] Example 4: In Example 4, compared with Example 1, the mixed polyester material obtained in the preparation of Example 2 in step A1 is replaced with the mixed polyester material obtained in the preparation of Example 3, and the other steps are the same.

[0035] Example 5: Compared with Example 1, Example 5 replaces the mixed polyester material obtained in Example 2 in step A1 with the mixed polyester material obtained in Example 4, while the other steps are the same.

[0036] Comparative Example 1: Compared with Example 1, the mixed polyester material obtained in preparation Example 2 in step A1 was replaced with the mixed polyester material obtained in Comparative Preparation Example 1, and the other steps were the same.

[0037] Comparative Example 2: Compared with Example 1, the mixed polyester material obtained in step A1 of Example 2 was replaced with the mixed polyester material obtained in Comparative Example 2, and the other steps were the same.

[0038] Comparative Example 3: Compared with Example 1, the vacuum annealing process in step A2 is omitted in Comparative Example 3. That is, the fiber is directly used for chopped board production without annealing after spinning and winding. The other steps are the same.

[0039] The waterproof and environmentally friendly polyester fiber sound-absorbing panels prepared in each embodiment and comparative example were subjected to performance testing: 1) Thickness and density: The thickness and density of the board were measured using digital calipers and an electronic balance.

[0040] 2) 24-hour water absorption rate: Immerse a 100mm×100mm sample in deionized water at room temperature for 24 hours, remove it, wipe off the surface moisture, weigh it, and calculate the water absorption rate.

[0041] 3) Bending strength: The three-point bending strength was determined using a universal testing machine with a span of 150 mm.

[0042] 4) Noise Reduction Coefficient (NRC): Referencing GB / T 20247-2006 Reverberation Chamber Method, the sound absorption coefficients at frequencies of 250Hz, 500Hz, 1000Hz, and 2000Hz were measured, and the arithmetic mean was calculated.

[0043] 5) Weighted sound insulation Rw: Measured and calculated using the double reverberation chamber method, referring to GB / T 19889.3-2026 standard.

[0044] 6) Dynamic mechanical loss factor tanδ: A 40mm×10mm×2mm sample was taken from the core of the sound insulation board and measured using a dynamic mechanical analyzer in tensile mode, under the conditions of 1Hz frequency, 25℃ temperature and 15μm amplitude.

[0045] The test results are shown in the table below: Table 1 Test Results

[0046] The test results shown in the table indicate that the examples and comparative examples are compared as follows: Example 2 adjusted the core-to-sheath volume ratio of the core-to-sheath fiber from 75:25 in Example 1 to 60:40. Increasing the sheath ratio increases the fiber sheath thickness and the proportion of a dense surface layer, improving the fiber's longitudinal bending stiffness. Simultaneously, the thicker sheath provides a stronger sound wave reflection barrier, increasing the weighted sound insulation. However, the increased sheath thickness correspondingly reduces the proportion of the core layer's microporous cross-sectional area, decreasing the number of closed-cell cavities within the fiber, lowering the sound wave scattering interface density, and reducing the noise reduction coefficient (NRC). The loss factor tanδ only decreased slightly because the DA cross-linking network still primarily exists in the core matrix. This indicates that the core-to-sheath volume ratio should be chosen in balance between sound insulation and sound absorption performance; 75:25 is more suitable for applications where sound absorption is the primary focus, while 60:40 is more suitable for applications with higher sound insulation requirements.

[0047] In Example 3, the amount of core-sheath microporous fiber was increased from 75 parts to 80 parts, while the amount of low-melting-point copolyester bonding fiber was reduced from 20 parts to 15 parts. The reduction in bonding fiber led to a decrease in the density of bonding points between fibers within the board, resulting in a slight decrease in the board's flexural strength, but still meeting the usage requirements. The reduction in binder increased the porosity between fibers, raising the noise reduction coefficient (NRC). However, insufficient bonding reduced the overall stiffness of the fiber network, shifting the board's resonant frequency to lower frequencies and decreasing the sound insulation (Rw). The loss factor (tanδ) decreased slightly because the sound absorption and damping functions mainly come from the microporous fibers themselves, and their increase compensated for the reduction in binder. This demonstrates that the amount of core-sheath microporous fiber is one of the key factors determining sound absorption performance, but it needs to be optimized in conjunction with the amount of binder to ensure sufficient mechanical and sound insulation performance.

[0048] Example 4 used the mixed polyester material prepared in Example 3, with the amount of bismaleimide (BMI) increased from 0.7 g in Example 1 to 1.0 g. Excessive BMI significantly increased the DA crosslinking density in the core matrix after annealing, raising the loss factor tanδ and enhancing damping performance, thus improving the sound insulation Rw of the board. However, the portion of excess BMI not fully dispersed during the high-temperature processing stage may form small, localized over-crosslinked regions during subsequent annealing, leading to a slight increase in fiber brittleness and a slight decrease in flexural strength. This indicates that the amount of BMI should be controlled to balance high damping and mechanical flexibility.

[0049] Example 5 used the mixed polyester material from Preparation Example 4, with the amount of bismaleimide reduced to 0.4 g. Insufficient BMI resulted in only some furan side groups participating in crosslinking after annealing, leading to a sparse crosslinked network and a significant decrease in the loss factor tanδ compared to Example 1. The sound insulation Rw also decreased accordingly, approaching that of the uncrosslinked Comparative Example 1. The noise reduction coefficient NRC remained essentially the same because the microporous structure was not affected by the crosslinking density. This demonstrates that a sufficient amount of BMI is necessary to construct an effective DA crosslinked network and achieve a significant improvement in damping performance.

[0050] Comparative Example 1 replaced the mixed polyester material with that of Comparative Preparation Example 1. The fiber core layer contained only furan copolyester without a crosslinking agent. No DA crosslinking reaction occurred during annealing, and the matrix remained a linear polymer with an extremely low loss factor (tanδ), showing very limited improvement compared to pure PET fiber. However, due to the inherent viscoelasticity of the flexible aliphatic segments in the furan copolyester, the tanδ was still slightly higher than that of pure PET. Regarding sound absorption and insulation, the fiber microporous structure and sheet forming process were the same as in Example 1, with little change in NRC and Rw. This fully demonstrates the crucial role of bismaleimide as a DA crosslinking agent in constructing a high-damping network; without the crosslinking agent, a qualitative change in performance cannot be achieved.

[0051] In Comparative Example 2, hydroquinone was omitted from the preparation of the mixed polyester material. During the high-temperature extrusion of the twin-screw extruder in step B3, the bismaleimide, lacking a free radical inhibitor, underwent self-polymerization in the melt above 250°C, generating irreversible polyimide. This resulted in only a small amount of residual free bismaleimide being able to undergo DA reaction with furan side groups during subsequent annealing, leading to an incomplete crosslinking network. Simultaneously, the irreversible rigid structure of the polyimide increased fiber brittleness, and the noise reduction coefficient slightly decreased due to damage to the microporous structure caused by local fiber fracture. This clearly demonstrates that adding a free radical inhibitor during the high-temperature processing stage is crucial for protecting bismaleimide from thermal self-polymerization and ensuring the efficiency of subsequent DA crosslinking.

[0052] Comparative Example 3 omitted the vacuum annealing process in step A2, and the fibers were directly used for board making after spinning and winding. Because the fibers were rapidly cooled after high-temperature spinning, the furan and bismaleimide were frozen in an unreacted state. Lacking the thermodynamic window and segment mobility provided by annealing, the DA crosslinking reaction was extremely slow at room temperature, and the crosslinking network was almost not formed. Therefore, the tanδ was extremely low, comparable to that of Comparative Example 1, indicating that the DA crosslinking function cannot be realized without annealing. The microporous structure of the fibers, the core-sheath configuration, and the board forming process were consistent with Example 1, with little change in other performance indicators, except for a slight decrease in sound insulation due to the lack of damping. This fully demonstrates that low-temperature solid-state annealing is an indispensable step in constructing the DA dynamic crosslinking network and injecting its high damping characteristics into the final product. This step successfully decouples the contradiction between high-temperature polyester processing and the low-temperature thermodynamic window of DA.

[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board, characterized in that: The process includes the following steps: Step S1: Weigh 75-80 parts by weight of sheath-core microporous polyester fiber short cuts and mix them with 15-20 parts of low melting point polyester fiber and 10 parts of polycaprolactone powder. The mixture is then fed into a fiber mixing and opening machine, combed, laid into a web and repeated to obtain a fiber web. Step S2: The fiber mesh is fed into a double-sided needle punching machine for pre-reinforcement. Then, 8 layers of pre-reinforced fiber mesh are stacked and hot-pressed. First, it is hot-pressed at a temperature of 75℃ and a pressure of 0.3MPa for 5 minutes, and then hot-pressed at a temperature of 90℃ and a pressure of 1MPa for 4 minutes. Then, water-based polyurethane emulsion is sprayed on its surface, and it is dried at 80℃ for 5 minutes. After cutting, a waterproof and environmentally friendly polyester fiber sound-absorbing board is obtained.

2. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 1, characterized in that: In step S1: the areal density of the fiber web is 300-320 g / m². 2 In step S2: the solid content of the waterborne polyurethane emulsion is 5%, and the spraying amount is 5 g / m². 2 .

3. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 1, characterized in that: The core-sheath microporous polyester fiber is obtained through the following steps: Step A1: Mix and dry the mixed polyester material, azodicarbonamide, zinc oxide and white oil to obtain the core layer foaming premix; mix and dry the polyethylene terephthalate-polyethylene glycol block copolyester and hydrophobic nano silica to obtain the skin layer premix. Step A2: Spinning is carried out using a core-sheath composite spinning machine. The core layer foamed premix and the sheath premix are fed into a twin-screw extruder and melt-extruded. The fibers are then produced by the spinneret, bundled, drawn and stretched, wound, and then sent to a vacuum oven for annealing to obtain core-sheath microporous polyester fibers.

4. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 3, characterized in that: In step A1: the amount used in step A1 is: 90-92 parts of mixed polyester material, 5 parts of azodicarbonamide, 1.5 parts of zinc oxide and 0.5 parts of white oil; the amount used in step A2 is: 98 parts of polyethylene terephthalate-polyethylene glycol block copolyester and 2 parts of hydrophobic nano silica. The polyethylene glycol content in its polyethylene terephthalate-polyethylene glycol block copolyester is 20wt%.

5. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 3, characterized in that: In step A2: the volume ratio of the core foam premix and the skin premix is ​​controlled by a metering pump to be 75:25 or 60:40; the melt extrusion temperatures of the core foam premix and the skin premix are 260℃ and 240℃, respectively; the spinneret has annular core-skin holes with 9 holes and a hole diameter of 0.3mm; the winding speed is 600m / min and the stretching ratio is 1.2 times; the annealing pressure is 100Pa, and during annealing, it is first held at 60℃ for 4h and then held at 90℃ for 20h.

6. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 1, characterized in that: The mixed polyester material is prepared by the following steps: Step B1: Diethyl itaconic acid, furfurylamine and acetic acid were mixed and reacted for 18 h under nitrogen protection, stirring at 300 rpm and temperature at 50 °C. After cooling, the mixture was washed with saturated sodium bicarbonate solution, separated, rotary evaporated and dried to obtain the side-chain furan monomer. Step B2: Hexanediol, 1,4-butanediol, side-chain furan monomer, n-butyl titanate and hydroquinone were mixed and stirred for 30 min under nitrogen protection at a stirring rate of 300 rpm and a temperature of 90℃. The temperature was then increased to 120℃ and stirred for 1 h. Finally, the temperature was increased to 190℃ and reacted for 4 h. The vacuum was drawn to a pressure of 100 Pa and reacted at 200℃ for 3 h. After cooling and drying, the side-chain furan copolyester was obtained. Step B3: Dry polyethylene terephthalate, side-chain furan copolyester and 4,4'-bismaleimide diphenylmethane and mix with antioxidant 1010, hydroquinone and calcium stearate, feed into a twin-screw extruder for melt extrusion, water-cooled granulation, and drying to obtain a mixed polyester material.

7. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 6, characterized in that: In step B1, the ratio of diethyl itaconic acid, furfurylamine, and acetic acid is 10g:5.2g:0.1mL.

8. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 6, characterized in that: In step B2, the ratio of hexanediol, 1,4-butanediol, side-chain furan monomer, n-butyl titanate, and hydroquinone is 4.5g:7g:3.2g:0.005mL:0.03g.

9. The method for preparing a waterproof and environmentally friendly polyester fiber sound-absorbing board according to claim 6, characterized in that: In step B3: the ratio of polyethylene terephthalate, side-chain furan copolyester, 4,4'-bismaleimide diphenylmethane, antioxidant 1010, hydroquinone, and calcium stearate is 7g:3.5g:0.7g:0.05g:0.005g:0.03g; the twin-screw extruder head temperature is 250℃, the screw speed is 200rpm, and the residence time is 2min.

10. A waterproof and environmentally friendly polyester fiber sound-absorbing board, characterized in that: Prepared according to any one of the preparation methods described in claims 1-9.